Defining self-disclosure of personal cancer coping experiences in oncology social workers' helping relationships: When cancer "hits home". Issue 3 (27th April 2022) - Lawson, Kimberly; Werner-Lin, Allison; Fitzgerald, Frances; Zabora, James Robert
Abstract: Purpose: Oncology social workers are increasingly finding themselves diagnosed with or caring for a loved one with cancer. Self-disclosure may be useful for building a therapeutic alliance. Yet, practice-informed guidelines for psychosocial oncology providers do not exist. Research Approach: Twenty-three psychosocial oncology providers diagnosed with and/or providing care to someone with cancer completed semi-structured interviews eliciting attitudes and utilization regarding self-disclosure. Methodological Approach: Interviews were digitally recorded and transcribed verbatim. Using grounded theory's constant comparative method, researchers conducted open and theoretical coding. Findings: Participants expressed consensus in defining, and reported a range of evolving practices regarding, self-disclosure. Recommendations for responsible self-disclosure included self-awareness, ongoing assessment, supervision, and enhanced educational programming. Interpretation and Implication: Therapeutic tools must evolve as core features of psychosocial oncology care. A flexible and context-specific framework for clinician self-disclosure related to personal experiences with cancer can guide oncology social work practice.